2016
DOI: 10.1097/ico.0000000000000921
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Factors Affecting Endothelial Cell Density in an Eye Bank Corneal Donor Database

Abstract: Age, race, ocular surgery (cataract and refractive), and DM seem to significantly affect donor corneal ECD. Of these variables, age, a history of cataract surgery, and DM were found to be the greatest risk factors for inadequate donor cell density (less than 2000/mm).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 35 publications
1
30
0
5
Order By: Relevance
“…[17,23]. Kwon et al fanden in einer binär logistischen Regressionsanalyse den Linsenstatus (p = 0,001) neben dem Spenderalter und dem Diabetes als Haupteinflussfaktor auf die Eignung [17]. Hornhäute, deren Spender sich zuvor einer Kataraktchirurgie unterzogen hatten, besaßen in 66,7 % der Fälle weniger als 2000 Zellen/mm².…”
Section: Einflussfaktoren Auf Die Kontamination Des Kulturmediumsunclassified
See 2 more Smart Citations
“…[17,23]. Kwon et al fanden in einer binär logistischen Regressionsanalyse den Linsenstatus (p = 0,001) neben dem Spenderalter und dem Diabetes als Haupteinflussfaktor auf die Eignung [17]. Hornhäute, deren Spender sich zuvor einer Kataraktchirurgie unterzogen hatten, besaßen in 66,7 % der Fälle weniger als 2000 Zellen/mm².…”
Section: Einflussfaktoren Auf Die Kontamination Des Kulturmediumsunclassified
“…[25]. Während das Geschlecht bei Kwon et al univariat einen Einfluss auf die Eignung aufwies (p = 0,012), zeigte es sich in der multivariaten Analyse nicht als signifikanter Beeinflusser [17]. Bei McGlumphy et al (p = 0,07) und Kwon et al (p = 0,012) lag der Einfluss des Geschlechts in der multivariaten Analyse zwar jenseits des Signifikanzniveaus (p ≥ 0,05), es war jedoch ein Trend zu erkennen [17,24].…”
Section: Einflussfaktoren Auf Die Verwerfung Wegen Positiver Spendersunclassified
See 1 more Smart Citation
“…It is suggested that continuous hyperglycemia leads to a decrease in corneal pre-KD and ECD after SMILE. Some studies showed that the decrease in ECD was positively correlated with the course of diabetes and that there was no signi cant change in ECD in patients with early diabetes 23 . After SMILE, there was no signi cant difference in ECD between G-B and G-C, as well as in each of the three groups before surgery, indicating that the SMILE operation itself did not lead to the decrease of ECD.…”
Section: Pre-kd and Ecdmentioning
confidence: 99%
“…A statistically significant relationship between age and endothelial cell density (ECD) was reported in numerous previous reports. 7 8 Murphy et al reported a 50.4% decrease in ECD in the foetus, an annual decrease of 17.73% in the early postnatal period between 0 and 2 years, and a 0.56% yearly reduction thereafter. The rapid decrease in cell density observed in utero and during the first 2 years of life is proportionally related to the degree of corneal growth.…”
Section: Introductionmentioning
confidence: 99%